Forgotten sins - Zanetti, Rebecca (Forever, 2014)
When her husband, who mysteriously disappeared two years earlier, is found at a crime scene with no memory of how he got there, Josie must help this man who has no recollection of their life together unravel his dangerous past to discover why he is being framed for murder.